Decomposition of social problems of management digitalization - A. V. Raychenko (Управление)
The decomposition of social problems of management digitalization has been proved, presented and investigated in the article, the directories and formats of their positioning have been selected and opened consistently. Key objects of the research are manifestations of influence of social problems on setting, development and implementation of programs of management digitalization, approaches, opportunities and examples of definition of options of their resolution. Conducted analysis and formulated conclusions allow us to create complete representation and to implement applied recommendations about selection, a research and solution influence of social problems on management digitalization of modern organization. This is especially relevant today, when national, sectoral and regional programs for the digitalization of the economy and management define one of the key trends in breakthrough socio-economic development.The examples of the manifestation, study and resolution of social problems of digitalization from the actual practice of managing leading, efficiently operating domestic enterprises in the real sector of their sectors have been analyzed. The presenting material has been collected, processed and adapted by the author in the process of development, implementation and maintenance of the use of organizational and methodological materials commissioned by these organizations, as part of the implementation of applied research. In the statement of the provisions of the article, the material has been also used, collected by the author on open resources and in the processes of interaction with organizations of the infrastructure, that are actively introducing and widely using digital products and databases in management practice. Carried-out analysis of specific material actually involved in the processes of enterprises and organizations allows us reliably, adequately and prospectively oriented to identify, evaluate and decompose the existing range of social problems of management digitalization.